2017
DOI: 10.3389/fpls.2017.00819
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Insights into WRKY3 and WRKY4 Transcription Factors to Unravel the WRKY–DNA (W-Box) Complex Interaction in Tomato (Solanum lycopersicum L.). A Computational Approach

Abstract: The WRKY transcription factors (TFs), play crucial role in plant defense response against various abiotic and biotic stresses. The role of WRKY3 and WRKY4 genes in plant defense response against necrotrophic pathogens is well-reported. However, their functional annotation in tomato is largely unknown. In the present work, we have characterized the structural and functional attributes of the two identified tomato WRKY transcription factors, WRKY3 (SlWRKY3), and WRKY4 (SlWRKY4) using computational approaches. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 115 publications
(155 reference statements)
0
24
0
Order By: Relevance
“…Of these three upregulated WRKY members only two members SolyWRKY33 and SolyWRKY37 were used for further studies. The functional characterization of the SolyWRKY4 (XP_004235494.1) has been already reported in our previous publication [ 61 ].The Blast-p program research in the NCBI protein database ( http://blast.ncbi.nlm.nih.gov/blast.cgi [ 62 ] was used to find sequential homologs for both SolyWRKY33 and SolyWRKY37. Blast annotations were filtered using subject to query coverage of >96% and with sequence identity > 62%.…”
Section: Methodsmentioning
confidence: 99%
“…Of these three upregulated WRKY members only two members SolyWRKY33 and SolyWRKY37 were used for further studies. The functional characterization of the SolyWRKY4 (XP_004235494.1) has been already reported in our previous publication [ 61 ].The Blast-p program research in the NCBI protein database ( http://blast.ncbi.nlm.nih.gov/blast.cgi [ 62 ] was used to find sequential homologs for both SolyWRKY33 and SolyWRKY37. Blast annotations were filtered using subject to query coverage of >96% and with sequence identity > 62%.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that all the replaced residues in the FOXG_04696 were present in either major or another major (first two) cavities predicted by the metapocket server. In our previous studies, the structure of the functional domain of the proteins that belong to the WRKY gene superfamily members has been modeled for its qualitative and quantitative evaluation, to unravel the DNA–protein interaction studies, in a stimulus-specific manner in tomato ( Aamir et al, 2017 , 2018 ). In our results, the computational screening revealed the docking site and energy score values for all the 37 fungicides, to evaluate their efficacy against the FOL pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be stressed that slight changes in the DNA-binding domain may have an important effect on the binding specificity, and sequence homologs may be highly similar yet have different functions ( Tao et al, 2009 , 2011 ; Du et al, 2014 ). For example, the close tomato homologs SlWKRY3 and SlWRKY4 are predicted to interact with the W-box DNA through a different motif, RKYGQK, and WRKYGQK, respectively ( Lai et al, 2008 ; Aamir et al, 2017 ). There is evidence that motifs outside the WRKY domain may provide binding specificity to WRKYs ( Phukan et al, 2016 ).…”
Section: Wrkys In Crosstalk Between Abiotic- and Biotic-stress Toleramentioning
confidence: 99%